A finite and stable exponential growth-adjusted indirect cost of cancer associated with discounted years of life lost in Saudi Arabia. Issue 5 (May 2018) - Da'ar, Omar B.; El-Metwally, Ashraf; Abu-Saris, Raghib; Jazieh, Abdul Rahman
Abstract: Background: The risk of getting cancer before full life expectancy and mortalities per year are on the rise in Saudi Arabia. Yet, evidence of economic burden of cancer in the country remains largely unknown. In order to provide evidence, we attempted to estimate the economic burden in terms of indirect cost associated with premature cancer deaths among the active or potentially economically active population aged 15–60 years in Saudi Arabia. Method: Within the framework of the World Health Organization guide of identifying the economic consequences of disease and injury, our method employs cost-of-illness approach. This approach is based on a macroeconomic model that estimates the indirect cost of cancer in terms of total non-health gross domestic product resource loss associated with a disease. We used epidemiological, health system, and macroeconomic data for our estimation. We discounted the net loss at 3% and computed an extension of the loss with a finite and stable upper limit proxied by non-health gross domestic product per capita. We carried out separate analyses for male and female. We conducted sensitivity analyses to account for uncertainties of epidemiological and economic factors on the robustness of the estimated economic burden. We varied the proportion of total cancer deaths, discount rate, and value of health expenditure per capita by ±20%. We further determined which of these factors or parameters had the greatest uncertainty or variation on the net present value total non-health gross domestic product resource loss per Capita. Results: Our results indicate the indirect cost associated with cancer deaths among Saudi population aged 15–60 years to be Int$ 2.57 billion of which Int$ 1.46 billion (57%) was accounted for by females. The total indirect loss of cancer deaths increased by 8% to Int$ 2.77 billion when the loss is allowed to grow with a finite and stable upper limit proxied by non-health gross domestic product per capita over the discounted years of life lost per a death among female and male respectively. Much of the uncertainty in the determination of the value of the loss was accounted for by the proportion of total cancer deaths and discount rate, while health expenditure per capita was responsible for the least variability. Conclusion: Our findings reveal evidence of indirect cost associated with cancer premature deaths in Saudi Arabia. In order to develop cancer control actions, the results of this study can inform health system policymakers not only of the extent of the enormous economic burden but also drawing attention to epidemiological and economic factors that explain the variability of the burden.